2019
DOI: 10.1186/s13019-019-0983-y
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality of serious gastrointestinal complications after lung transplantation

Abstract: BackgroundGastrointestinal complications after lung transplatation are associated with an increased risk of morbidity and mortality. This study aims to describe severe gastrointestinal complications (SGC) after lung transplantation.MethodsWe performed a prospective, observational study that included 136 lung transplant patients during a seven year period in a tertiary care universitary hospital. SGC were defined as any diagnosis related to the gastrointestinal or biliary tract leading to lower survival rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Serious gastrointestinal complications, such as diverticulitis, are common after lung transplant and are associated with considerable increases in morbidity and mortality. 14,15 The incidence of posttransplant diverticulitis in our cohort (3.32%) was lower than the findings of the most recent studies (4.4%-12.4%) 6,12,16 ; however, it is much higher than that reported in the general population (0.7%). 17 Our results are consistent with previous studies reporting that over 60% of diverticulitis cases occur within 2 years of transplant.…”
Section: Discussioncontrasting
confidence: 78%
“…Serious gastrointestinal complications, such as diverticulitis, are common after lung transplant and are associated with considerable increases in morbidity and mortality. 14,15 The incidence of posttransplant diverticulitis in our cohort (3.32%) was lower than the findings of the most recent studies (4.4%-12.4%) 6,12,16 ; however, it is much higher than that reported in the general population (0.7%). 17 Our results are consistent with previous studies reporting that over 60% of diverticulitis cases occur within 2 years of transplant.…”
Section: Discussioncontrasting
confidence: 78%
“…Several studies have reported abdominal complications of varying severity at a rate of 21 to 62% after LTx. [21,22] Prolonged operative time, postoperative epidural analgesia, immunosuppressive drugs, and electrolyte imbalance play a role in these complications. [23] In the present study, the rate of GI complications was higher among patients receiving a higher amount of fluid (Group 2).…”
Section: Discussionmentioning
confidence: 99%
“…Peptic ulcer disease was also a risk for mortality in our study. It is reported from small series to occur and reoccur after transplantation and may lead to intestinal perforation ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%